Stochastic Estimation of Seroprevalence Against Ornithobacterium rhinotracheale and Avian Pneumovirus among Chickens in Argentina - Uriarte, J.; Suzuki, K.; Origlia, J.; Gornatti, D.; Piscopo, M.; Cerda, R.; Herrero, M.; Marcantoni, H.; Unzaga, M.F.; Spinsantti, E.; Marino, F.; Pecoraro, M.; et al. (International Journal of Poultry Science, 2010)
The objective of this study was to estimate the true prevalence of seropositive individual chicken against Ornithobacterium rhinotracheale and avian pneumovirus in Argentina, using the Rogan-Gladen estimator in combination with Bayesian inference. Chicken runs existed in 21 and 20 different towns in Buenos Aires and Entre Ríos Provinces in Argentina for Ornithobacterium rhinotracheale and avian pneumovirus seroprevalence, respectively, were studied. Individual-chicken sera were analyzed using a commercial enzyme-linked immunosorbent assay. The 719 (for testing Ornithobacterium rhinotracheale) and 933 (for testing avian pneumovirus) chickens were investigated. The overall true seroprevalence was 62.6% [95% Bayesian Credible Interval (BCI): 37.6-84.5%] and 8.0% (95% BCI: 1.4-18.5%) against Ornithobacterium rhinotracheale and avian pneumovirus, respectively.